2020
DOI: 10.21203/rs.3.rs-28633/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors for perineal and vaginal tears in primiparous women – a prospective cohort study

Abstract: BackgroundThe aim of this study was to estimate the incidence of second-degree perineal tears, obstetric anal sphincter injuries, and high vaginal tears in primiparous women, and to examine how sociodemographic and pregnancy characteristics, hereditary factors, obstetric management and the delivery process are associated with the incidence of these tears.MethodsAll nulliparous women registering at the maternity health care in Region Örebro County, Sweden, in early pregnancy between 1 October 2014 and 1 October… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…This is because as the gestational age increases, the estimated fetal weight increases, with increased risk of perineal injury during delivery. Studies in Sweden, [20] and Italy [21] have reported a significant association between fetal macrosomia (birth weight ≥ 4.0kg) and severe perineal tear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because as the gestational age increases, the estimated fetal weight increases, with increased risk of perineal injury during delivery. Studies in Sweden, [20] and Italy [21] have reported a significant association between fetal macrosomia (birth weight ≥ 4.0kg) and severe perineal tear.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal macrosomia (estimated fetal weight ≥ 4.0kg) has been reported by various studies as a significant risk factor for OASI. A study in Sweden on pelvic floor in pregnancy and childbirth (POPRACT), reported a highly significant association with an odds ratio of 6.02 (2.32, 15.6) [20]. Another study in San Gerardo Hospital in Italy reported risk factors for 3 rd and 4 th degree perineal tear as birth weight > 4kg, shoulder dystocia, prolonged second stage of labour, and delivery after 40 weeks gestation [21].…”
Section: Introductionmentioning
confidence: 99%
“…Perineal tears affect 85% of women during childbirth to varying degrees; this includes episiotomy wounds. 1 The incidence of second-degree tear, that is a tear involving the perineal muscles but not involving the anal sphincter, has been reported to be between 35.1%-78.3% in primiparous and 34.8-39.6% among multiparous patients [4] . The data on the number of patients developing wound dehiscence is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Perineal trauma is influenced by ethnicity, and a link has been shown between Asian ethnicity and severe perineal trauma. First pregnancy, maternal age of more than 30 years, a big infant (both in terms of weight and head size), a protracted second stage, and malposition all enhance the risk of perineal damage [9,10].…”
Section: Introductionmentioning
confidence: 99%